Nonenzymatic glycosylation of tissue and blood proteins. - (:unkn) unknown (My University, 1996)
A brief description of the phenomenon of nonenzymatic glycosylation will be presented, some examples given from the literature and then a brief summary of the results of laboratory research conducted in this area by myself and coworkers since 1981. Excessive glycosylation causes undesirable changes in proteins. Such glycosylation also occurs to collagen in oral tissue. In a study on induced experimental diabetes in rats we observed a defective platelet aggregation curve for gingival collagen. Glycosylation of proteins is known to result in functional defects, for example hemoglobin acquires an increased affinity for oxygen. Glycosylation of rat and bovine lens crystallins has been reported as being an important genesis of cataracts in diabetes. Increased glycosylation of submandibular collagen has been shown to occur in diabetes. However collagen from normal subjects has also been found to show an age related advanced glycosylation end product pigment. Increased platelet membrane protein glycosylation has been reported and the hyperaggregation typically observed in these cases thought to be due to glycosylation. The presence of red cell membrane proteins has also been reported and the impairment of red cell function in diabetes has been reported in cases of excessive glycosylation. According to some investigators cataract formation is prevented by some specific drug which inhibits the glycosylation of lens crystallins. Vitamin C has lowering effects on nonenzymatic glycation. Dentists should take into account the possibility of glycosylation of oral proteins such as collagen in cases of impaired gingiva tooth connection.